Osmanlı modernleşme sürecinde ilköğretim (1869-1922) - Nurdoğan, Arzu M., (Nurdoğan Demirkıran, Arzu Meryem) (My University, 2005)
Osmanlı Modernleşme Sürecinde İlköğretim (1869 - 1922) başlıklı tez, Osmanlı eğitim sisteminin başlangıcı olan ilköğretim kademesindeki temel dinamikleri ve modernleşme hareketlerini bütün boyutlarıyla inceleyebilmek amacıyla 7 bölümde kaleme alınmıştır. Tanzimat öncesi ve sonrasındaki ilköğretimin amaçları, kurumsal yapısı ve duraklama aşamalarının irdelenmeye çalışıldığı birinci bölümün ardından, ikinci bölümde Osmanlı ilköğretimini uzun yıllar yönlendirecek olan ve daha önce bu alanda atılan gelişmelerin ilk defa sistemleştirildiği yıl olan 1869'dan itibaren, merkez ve taşra eğitim idaresindeki bürokratikleşme süreci incelenmiştir. Yeni kurulan ilköğretim okullarının teşkilat ve idare yapısı, öğretmen ve öğrenci keyfiyeti, eğitim - öğretimin niteliği, bina, ders araç - gereç özellikleri üçüncü bölümün konusu olmuştur. İmparatorluğun ilköğretim politikasının mali kaynaklarına temas edilen dördüncü bölümün ardından, Osmanlı ilköğretim sistemine ilişkin klasik yaklaşımların dışında farklı anlayışların geliştirilmesi ve siyasi akımların ders kitaplarına etkisi beşinci bölümde incelenmeye çalışılmıştır. Altıncı bölüm, imparatorluğun kozmopolit nüfus yapısının ve yabancı okulların, ilköğretimin modernleşme sürecindeki rolünü ortaya koyma amacıyla hazırlanmıştır. İlköğretimdeki modernleşme süreci hakkında daha gerçekçi varsayımlar, tespitler geliştirebilmek ve yorumlar yapabilmek için son olarak okul izlenimleri bölümü kaleme alınmaya çalışılmıştır.

The term of education, is derived from educare in Latin, means to rear, to bring up or to improve. But at the same time the meaning of education in all its rich variety, above all the connection with learning and teaching, there is no specific definition about education. Nevertheless, without any very clear idea education is accepted as a main human activity, which during the mankind history in its legal - illegal, systematic - unsystematic and objectively - unobjectionably practices were determined. There are few who would argue with the notion of education has played a critical role in the modernization of the Ottoman Empire. Indeed, it is both methodological issue writing the thesis of modernization and settling the attitude of Turkish modernization. The modernization is a variable within so many parameters in the context of Westernization or in the other scopes. As one of main element of this variable education, has been placed the second part of the Ottoman researches. However, it is essential that giving up historiography as a definer, descriptor and storyteller instead interpreter, comprehensive and problem solver, which means, the contribution of education as fundamental as political, military and economical elements in Ottoman modernization and indeed, creation of the modern world. This thesis is the result of an interest in the subject of the role of education in the Ottoman modernization. It is hoped that this research helps to explain why the attempts of Ottoman modernization were not reach its aim. It might be a mistake to expect an acquired scientific and rational mentality in Ottoman education as a result of the attempts at modernization of education, because it was not overcame the traditional structure of Islamic thesis above elementary education until the end of empire. Further, while the main stress on the centralist politics since 19th century, special attention into the elementary education is directed to spreading through the symbols of legitimate. This study focuses on two aspects of Ottoman modernization of primary education: the use of education by a state as a tool for achieving certain goals in order to recover empirial unity, and the reorganization of curriculum and schooling. The complexity of the material covered here is such that only two arrangements - the originality and the objectivity - seemed practical. The Bibliography will bear witness to the extent which I am selected for the work of many others which is relevant to my subject. According to the researches about Ottoman social structure, Tanzimat Era was defined as a period, which was appeared a new mankind-type into the Ottoman social life. The completion of this study represents an investigation of both alterations and affects in education of the new mankind-type. Faced with an unaware population of the meaning or significance of education, the Ottoman Empire conceived the inevitability of getting primary education into a state policy while the financial crises took shape over the whole empire. This research shows, how the primary education was changed in practice, from indoctrination of orthodox -Islamic values into the accumulation of political ideology, belief, and ethics. Regarding of this content, the core of the present study is the development of curriculum and schooling.
Keywords: İlköğretim_Türkiye_Tarih; Osmanlı Devleti_İlköğretim